Role of Artificial Intelligence in FINTECH and its Impact in Banking Sector (Journal of Informatics Education and Research, 2024)
Artificial intelligence (AI) is the act of instructing a computer, robot, or other object to behave in a smart human way. AI is the study of how the human mind works, how it learns, how it makes decisions, and how it provides outputs. This study is dealing with the idea of AI in the banking system, how it has changed banking, and how it influence human labor. We all are aware that humans make mistakes, but as technology evolves, there is a lack of talented employees to control automation. Certain process and manual tasks that were formerly undertaken by individuals are being replaced by automated machines powered by technology. AI helps banks manage high-speed, record-level data and get valuable insights. This report provides an overview of current AI applications in the banking industry and how they are changing the nature of banking in India. The banking sector is making considerable transformation at a fast rate. Since AI in banking apps isn't only used in retail banking, banks may use it to provide frictionless, 24/7 interactions with customers. All other banking markets, including backend and mid office of investment banking, may benefit from AI.